The Reproduction and Evolution of Institutional Logics: A practice-centric perspective - Schildt, Henri; Kodeih, Farah (Organization Theory, 2025)
The institutional logics perspective has been one of the most prominent theories within organization and management research. It bridges different levels of analysis and explains how culture both enables and constrains collective and individual actors. Yet, despite abundant research on institutional plurality and complexity, limited attention has been paid to the dynamics through which specific institutional logics are reproduced and evolve over time. Furthermore, even as researchers have recognized the importance of practices to institutional logics, they have often privileged beliefs, values, and discourses over practices—risking an overemphasis on abstract ideas, which Bourdieu termed the “scholastic fallacy.” In this essay, we offer a practice-centric conception of institutional logics as a novel and complementary lens. Such a perspective is particularly valuable in the era of late modernity, where polarization and fragmentation have left many domains devoid of widely shared and agreed-upon meta-narratives or guiding ideals—often considered central to institutional logics. We elaborate how an identifiable institutional logic may instead emerge from a network of interconnected practices bound together by common constitutive elements (such as meanings and material elements), practitioners, and referential linkages. We further show how such a practice-centric perspective offers insights into the broader evolution of institutional logics. Finally, we discuss how political struggles over practices can shape an institutional logic, outlining praxis as an important but often unacknowledged arena of cultural contestation.